Decision support system for university campus quality of life evaluation based on users’ perception : a case study applied to the Campus of the University of Minho - Rodrigues, Daniel Souto (2008)
This paper presents the work that conduced to the development of an information system to evaluate and monitor university campi quality of life. The system embodies two main functions: to provide information to the community and to support campus planning and management. Using a scenario describing possible actions, some users evaluated how its implementation would interfere with the quality of life on the campus. Results showed that it would produce a global improvement, in comparison to the year of the study.